Q. 1 Q4.3( 7 Votes )

<span lang="EN-US

Answer :

If LHS is


(x – 4) (x – 2)


Then RHS would be


(x – 4) (x – 2)


= x2 – 4 × x – 2 × x + (-2) × (-4)


= x2 – 4x – 2x + 8


= x2 – 6x + 8


The error is x2 – 6x + 8 instead of x2 – 8


Hence (x – 4) (x – 2) = x2 – 6x + 8


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Quiz | Questions on FactorizationQuiz | Questions on FactorizationQuiz | Questions on Factorization41 mins
NCERT | Factorisation ProblemsNCERT | Factorisation ProblemsNCERT | Factorisation Problems38 mins
Quiz | Important Questions on FactorisationQuiz | Important Questions on FactorisationQuiz | Important Questions on Factorisation35 mins
Algebraic Identities - Mark your Weak AreasAlgebraic Identities - Mark your Weak AreasAlgebraic Identities - Mark your Weak Areas41 mins
Champ Quiz | Division of PolynomialsChamp Quiz | Division of PolynomialsChamp Quiz | Division of Polynomials33 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics